Hereditary hemorrhagic telangiectasia, embolization, and Young's procedure: oral surgical management - Malthiery Eve; de Thierrens Carle Favre; Bouchiha Kevin; Levallois Bernard; Torres Jacques-Henri; Fauroux Marie-Alix (EDP Sciences, 2018)
Hereditary hemorrhagic telangiectasia (HHT) case with history of embolization and Young's procedure: surgical management. Introduction: Osler-Weber-Rendu disease hereditary hemorrhagic telangiectasia (HHT) is a genetic vascular dysplasia. It causes hemorrhagic manifestations, cutaneous and mucosal telangiectasia and visceral vascular shunts, which sometimes lead to brain abscesses after dental avulsion. Acute epistaxis can be managed by vascular ligature or selective embolization. In rare cases, management can even go as far as nasal closure. Observation: A case of five dental avulsions is described, in a patient affected by HHT who previously underwent a bilateral embolization in the area of the facial artery as well as Young's procedure for frequent epistaxis. Comments-Conclusion: The management of patients affected by HHT needs rigorous hemostatic methods and outpatient postoperative monitoring. Additionally, the remarkable imaging from panoramic radiography used in this case was instrumental in keeping track of embolization, by clearly highlighting the arterial pathways.